Growth Characteristics of Vitis vinifera L. cv. Cape Riesling - De La Harpea, A. C.; Visser, J. H. (South African Journal of Enology and Viticulture, 2017)
The effect of topping on the growth behaviour of Vitis vinifera L. cv. Cape Riesling vineyard was investigated. Shoot and leaf growth of both topped and untopped vines, can be described as sigmoidal. Shoot (cm) and leaf growth (cm') of the topped vines were significantly more than that of the untopped vines and are attributed to lateral shoot growth. Topping had no effect on bunch development. The development of skin, pulp and seed of both topped and untopped vines expressed as a percentage dry mass per berry can be described by a hyperbolic function for the skin, linear for the pulp and parabolic for the seed.